2019
DOI: 10.1113/jp277657
|View full text |Cite
|
Sign up to set email alerts
|

Cycling with blood flow restriction improves performance and muscle K+ regulation and alters the effect of anti‐oxidant infusion in humans

Abstract: Key pointsr Training with blood flow restriction (BFR) is a well-recognized strategy for promoting muscle hypertrophy and strength. However, its potential to enhance muscle function during sustained, intense exercise remains largely unexplored.r In the present study, we report that interval training with BFR augments improvements in performance and reduces net K + release from contracting muscles during high-intensity exercise in active men.r A better K + regulation after BFR-training is associated with an ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(120 citation statements)
references
References 51 publications
8
110
1
1
Order By: Relevance
“…The present study demonstrates that training with a substantial reduction (ß50%) in blood flow to exercising muscles (Christiansen et al 2019b) increases leg convective O 2 transport during both low-(23%) and high-intensity (13%), submaximal exercise in recreationally trained men (V O 2 max = 50 mL kg −1 min −1 ) ( Fig. 1).…”
Section: Bfr-interval Training Increases Leg Convective O 2 Transportsupporting
confidence: 54%
“…The present study demonstrates that training with a substantial reduction (ß50%) in blood flow to exercising muscles (Christiansen et al 2019b) increases leg convective O 2 transport during both low-(23%) and high-intensity (13%), submaximal exercise in recreationally trained men (V O 2 max = 50 mL kg −1 min −1 ) ( Fig. 1).…”
Section: Bfr-interval Training Increases Leg Convective O 2 Transportsupporting
confidence: 54%
“…Prior training studies performing repeated sprints in hypoxia have eluded to increased variation in perfusion during both leg cycling 4 and double poling. 10 Similar research has shown this response during acute leg cycling RST with different levels of BFR, 2 as well as after 6 weeks of single-leg cycling with BFR performing 3 sets of 3 × 2 min interval training, 24 and additionally with 4 weeks of single-leg knee extension with BFR. 25 The present arm cycling result was therefore expected.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, several studies demonstrate that reduced blood flow to the exercising limbs produces beneficial adaptive responses that are likely to be responsible for speeded V̇O2normalp kinetics, such as increased muscle oxidative enzyme activity, capillary density in quadriceps (Conceição et al., ; Esbjörnsson et al., ) and enhanced microvascular filtration capacity in humans (as an index of capillarity; Evans et al., ). Together, these factors might be responsible for speeding V̇normalO2 kinetics (Rossiter, ) and increasing V̇O2 peak and exercise tolerance (Abe et al., ; Kancin & Strazar, 2011; Christiansen et al., ; de Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Low‐intensity resistance or endurance exercise training, combined with blood‐flow restriction (BFR), is used as an alternative training method to accrue beneficial muscular training adaptations, among other benefits, especially in those for whom high‐mechanical loads are contraindicated. In particular, endurance BFR training increases several indices of aerobic function, including V̇O2max (Abe et al., ; de Oliveira, Caputo, Corvino, & Denadai, ; Park et al., ), exercise tolerance (Abe et al., ; Kancin & Strazar, ; de Oliveira et al., ) and intramuscular adaptations supporting endurance exercise (Christiansen, Eibye, Hostrup, & Bangsbo, ; Christiansen et al., ; Christiansen, Murphy, Bangsbo, Stathis, & Bishop, ). The potential mechanisms responsible for increased V̇O2max and exercise tolerance are debated, but include the following: increased stroke volume and cardiac output (Park et al., ); increased muscle capillarity and diffusive oxygen transport (Esbjörnsson et al., ; Evans, Vance, & Brown, ; Kacin & Strazar, ); and increased muscle oxidative enzyme activity (Esbjörnsson et al., ; Kaijser et al., ).…”
Section: Introductionmentioning
confidence: 99%